Loss of the Periplasmic Chaperone Skp and Mutations in the Efflux Pump AcrAB-TolC Play a Role in Acquired Resistance to Antimicrobial Peptides in Salmonella typhimurium - Kapach, Gal; Nuri, Reut; Schmidt, Christiane; Danin, Adi; Ferrera, Shir; Savidor, Alon; Gerlach, Roman G.; Shai, Yechiel (Frontiers in Microbiology, 2020)
Bacterial resistance to antibiotics is a major concern worldwide, leading to an extensive search for alternative drugs. Promising candidates are antimicrobial peptides (AMPs), innate immunity molecules, shown to be highly efficient against multidrug resistant bacteria. Therefore, it is essential to study bacterial resistance mechanisms against them. For that purpose, we used experimental evolution, and isolated a Salmonella enterica serovar Typhimurium resistant line to the AMP 4DK5L7. This AMP displayed promising features including widespread activity against Gram-negative bacteria and protection from proteolytic degradation. However, the resistance which evolved in the isolated strain was particularly high. Whole genome sequencing revealed that five spontaneous mutations had evolved. Of these, three are novel in the context of acquired AMP resistance. Two mutations are related to the AcrAB-TolC multidrug efflux pump. One occurred in AcrB, the substrate-binding domain of the system, and the second in RamR, a transcriptional regulator of the system. Together, the mutations increased the minimal inhibitory concentration (MIC) by two-fold towards this AMP. Moreover, the mutation in AcrB induced hyper susceptibility towards ampicillin and colistin. The last mutation occurred in Skp, a periplasmic chaperone that participates in the biogenesis of outer membrane proteins (OMPs). This mutation increased the MIC by two-fold to 4DK5L7 and by four-fold to another AMP, seg5D. Proteomic analysis revealed that the mutation abolished Skp expression, reduced OMPs abundance and increased DegP levels. DegP, a protease which was reported to have an additional chaperone activity, escorts OMPs through the periplasm along with Skp, but is also associated with AMP resistance. In conclusion, our data demonstrate that both loss of Skp and manipulation of the AcrAB-TolC system are alternative strategies of AMP acquired resistance in Salmonella Typhimurium and might represent a common mechanism in other Gram-negative bacteria.